Critical notes on communication policies in platform capitalism in Latin America - Aminahuel, Aimé (2024)
The debate on public policies and regulations for digital platforms constitutes an urgent topic for communication sciences. This article aims to provide a theoretical-analytical approach to emerging dimensions in research on communication policies in platform capitalism in Latin America. The work is part of a critical approach to the political economy of communication, offers a state of the art and includes a bibliographic systematization of the main debates on the State, big tech and public policies. Reflections from the notions of cognitive capitalism and platform capitalism allow us to confront the instrumental theoretical approaches that characterize the study of internet intermediaries. Likewise, the paper problematizes the dilemmas posed by regulatory proposals based on a review of state initiatives and judicial decisions in Latin America. The final discussion addresses the challenges and tensions for research on communication policies on digital platforms in Latin America, such as the need to build a map of concepts and actors for the analysis of cases in the field of politics, legislation and economics of communication.